Customer Co-Creation and Exploration of Emerging Technologies: The Mediating Role of Managerial Attention and Initiatives. Issue 2 (April 2017) - Khanagha, Saeed; Volberda, Henk; Oshri, Ilan
Abstract : Prior research has emphasized the importance of organizational focus on exploratory behavior in response to the emergence of a revolutionary core technology and the associated uncertainties. The question of why some organizations are more successful than others at realizing and reacting to such a need has not yet been fully addressed. In particular, empirical evidence on the effects of customer orientation on the effectiveness of organizational responses to major technological changes is somewhat mixed. We develop and test a theoretical argument in which we emphasize an indirect link between customer involvement in innovation processes and exploratory behavior in emerging technology fields. In so doing, first we illustrate the part played by two managerial factors — attention to the technology and the introduction of non-routine organizational adaptations — in enabling exploratory activities such as experimentation and search for unfamiliar knowledge in a new technology field. Second, we discuss how customer co-creation contributes to both of these managerial factors and, consequently, indirectly stimulates exploratory behavior in these conditions. We provide empirical support for our related theoretical framework by means of six case studies and a survey among 131 companies that were adopting a similar emerging technology; i.e., Cloud computing.